(x^a)(x^b)=x^(a+b)
(ab)(cd)=(a)(b)(c)(d)
x^-m=1/(x^m)
(3y^-4)(2y^-4)=
(3)(y^-4)(2)(y^-4)=
(6)(y^-8)=
6/(y^8)
Answer:
![r(s(3))=7](https://tex.z-dn.net/?f=r%28s%283%29%29%3D7)
Step-by-step explanation:
we have
![r(x)=x^{2} +2x-1](https://tex.z-dn.net/?f=r%28x%29%3Dx%5E%7B2%7D%20%2B2x-1)
![s(x)=x-1](https://tex.z-dn.net/?f=s%28x%29%3Dx-1)
we know that
The function composition is equal to
(r ∘ s )(x) = r(s(x))
In the function r(x) substitute the variable x by the function s(x)
so
![r(s(x))=(x-1)^{2} +2(x-1)-1](https://tex.z-dn.net/?f=r%28s%28x%29%29%3D%28x-1%29%5E%7B2%7D%20%2B2%28x-1%29-1)
For x=3
substitute the value of x=3 in the function composition
![r(s(3))=(3-1)^{2} +2(3-1)-1](https://tex.z-dn.net/?f=r%28s%283%29%29%3D%283-1%29%5E%7B2%7D%20%2B2%283-1%29-1)
![r(s(3))=(2)^{2} +2(2)-1](https://tex.z-dn.net/?f=r%28s%283%29%29%3D%282%29%5E%7B2%7D%20%2B2%282%29-1)
![r(s(3))=4+4-1](https://tex.z-dn.net/?f=r%28s%283%29%29%3D4%2B4-1)
![r(s(3))=7](https://tex.z-dn.net/?f=r%28s%283%29%29%3D7)
Answer:
(7,7)
Step-by-step explanation:
Because going up would be moving along the y-axis, then you would add 5 to the Y value which was 2 so therefore, if you move up 5 you'll be at (7,7).:)
Answer:
diameter of the pizza = 21.88 centimeters
Step-by-step explanation:
Given:
C = d^2 – 2d + 447
where
C = cost of the pizza
d = diameter of the pizza
If the pizza costs $12.00, then what is a reasonable estimate for the diameter of the pizza?
12 = d^2 – 2d + 447
d^2 - 2d = 447 - 12
d^2 - 2d = 435
d^2 - 2d - 435 = 0
Solve the quadratic equation using formula
a = 1
b = -2
c = -435
d = -b +or- √b^2 - 4ac / 2a
= -(-2) +or- √(-2)^2 - (4)(1)(-435) / 2(1)
= 2 +or- √4 - (-1740) / 2
= 2 +or- √4 + 1740 / 2
= 2 +or- √1744 / 2
= 2 +or- 4√109 / 2
= 2/2 +or- 4√109/2
= 1 +or- 2√109
d = 1 + 2√109 or d = 1 - 2√109
= 1 + 2(10.44) or d = 1 - 2(10.44)
= 1 + 20.88 or d = 1 - 20.88
d = 21.88 or -19.88
diameter of the pizza = 21.88 centimeters
Therefore, the estimated diameter of the pizza can not be negative. So, diameter of the pizza = 21.88 cm